Epoxidized Olive Oil as a Sustainable Plasticizer to Polylactic Acid - Jabbar, Fayq Hsan; Mohammed, Fadhil Muhi (Iraqi Journal of Science, 2024)
The consumption of synthetic, non-biodegradable polymer plastics has drawn attention to growing environmental concerns, prompting the development of other materials, particularly bio-based materials. Biopolymer-based biocomposite materials are plasticized to improve their ductility. In this study, five distinct weight ratios of biopolymers (PA/EOO), 90 wt.%, 80 wt.%, 70 wt.%, 60 wt.%, and 50 wt.% were employed as plasticizers for poly-lactic acid (PA) in a fluid molding process. The mechanical, thermal stability, and morphological characteristics of the blends were each examined using a viscometer measurement (R.V.), tensile properties (TP), a scanning electron microscope (SEM), and a thermogravimetric analyzer (TGA). All composite materials (PA/EOO) mixtures show notable improvements in mechanical properties and excellent thermal stability when compared to pure PA. The maximum PA/EOO elongation at break was around 213 % when the PA/EOO mix was 80 wt %. Attractive morphological results from composite materials (PA/EOO) blends showed that EOO was compatible with PA and that the resulting composite material (PA/EOO) was thought to be an ecologically beneficial mixture because it contained vegetable oil.